Description of Phonology, Characteristics, and Determination of the Origin Language of Waisika - Agus Anggayana, I Wayan; Suparwa, I Nyoman; Dhanawaty, Ni Made; Budasi, I Gede (e-Journal of Linguistics, 2021)
This study aims to describe the Waisika language carried out in the Northeast Alor sub-district based on the observation point, which was the object of research. This research uses quantitative and qualitative approaches. In diachronic research methods, there are two main methods in facilitating the direction of research, namely quantitative methods and qualitative methods. Application of minimal pairing procedures and similar environments, it can be found that all vocoids sound in Waisika is vocal segments /a, i, u, e, o/. Application of minimal pairing procedures and similar environments, it can be found that all contoid sounds are consonant segments [p, b, m b, t, n t, d, k, g, n d, h, s, m, n, N, N k, l, r, w]. Five vowel phonemes, which are found to have complete distribution at the front, central, and back of the morpheme. The phoneme / m b/, / n t/, /d/, /k/, / n d/, /r/, /w/ only exists in the initial and middle position of words. The phonemes / N k/ are only in the central position of words. The phonemes /N/ are only in the central and back positions.